A feasibility study on the production of semi-refined carrageenan in the Bicol region - Alsua, Agnes Eliza (College of Engineering, 2002)
The project development and management study was conducted to determine the feasibility of setting up a semi-refined carrageenan facility, in the Bicol region. The project study is composed of 5 sections, specifically, Market Study, Technical Study, Organizational Study, Financial Study, and Social Profitability Analysis. The Market Study was conducted to ensure that there was a steady demand for the product. The analysis was done first by determining the nature, applications, and the corresponding demand for semi-refined carrageenan in the Philippines and the world. Forecasting was performed to ensure that there was a favorable market potential for the product in the future. After determining the demand for the product, an appropriate marketing plan was developed to ensure the success of the product in the local market. The technical study determined the methods, resources and facilities necessary for the production of semi-refined carrageenan in the Bicol region. The Technical Study discusses in detail, the production process, material requirements, equipment and tooling requirements, capacity plan, production labor needs, production planning, and facilities and design for the processing of the product. A cost analysis was conducted to determine the initial investment and operational expenditures ad an aid in the Financial Study. The Organizational Study determined the form of ownership to be adapted in the project, in this case a corporation. It was determined that this would be the best organizational structure that would best support of the objectives and requirements of the project. The Financial Study determined the project's total cost, the alternative sources of financing available, and the commercial profitability of the project. A decision was made as to what level and forms of financing was to be adapted. The financial analysis performed included testing the performance of the project against financial measures. A sensitivity analysis was conducted for further analysis. The Social Profitability Analysis determined the social attractiveness of the project based on its socio-economic contributions and the costs and benefits that it would induce on the external environment. It was determined that the project had a significant positive gain in the society and economy. The evaluation of the market technical, organizational, financial, and social profitability studies conducted established the overall feasibility of the profitability, and as will be proven in the following discussions.